Bio-Waste Management in Razi University by production of Leaf Mulch for the first time in world - Mohebi, Zahra; Sharifzadeh, Esmail; Ebadi, Hadi (Universitas Diponegoro, 2022)
Mulch is a type of protective covering placed on or spread over the soil surface. Mulches can be organic or inorganic and are available in many forms. Plastic film, proprietary mulch fabric, pinebark, straw, wood chips, newspaper, bark, grass clippings and leaf litter are examples. The use of tree leaves as mulch is very important to maximize the use of bio waste and reduce the environmental impact of waste and it is seen as both economically and environmentally sensible. Therefore, Leaf Mulch was produced for the first time in the world at Razi University by designing devices and using the technical knowledge of researchers. The aim of Leaf Mulch production, in addition to the optimal use of bio waste, was to maintain soil water, strengthen soil, control weeds and balance in soil temperature.Keyword: Bio-Waste Management, Leaf-Mulch, Maintain soil water, Strengthen soil